Energy harvesting concrete - Tan, Xin Bei (Nanyang Technological University, 2022)
The thermoelectric properties of Portland concrete were reported to be able to enhance with the addition of fibre. However, despite metakaolin-based geopolymer was reported to be a thermoelectric material with better thermoelectricity properties than Portland concrete, there was no investigations on further enhancement through addition of fibre yet. Therefore, this Final Year Project (FYP) study aims to discover the effect of carbon fibre on thermoelectric properties of Metakaolin-based geopolymer. Results of the project show that the addition of carbon fibre has positive effect on the Metakaolin-based geopolymer. With addition of carbon fibre of only 0.01 weight percentage of geopolymer mix, a high Seebeck coefficient of 3450 μV/°C was obtained, which is 2 times higher than the normal metakaolin-based geopolymers. Furthermore, the addition of carbon fibre was also reported to have positive effect on the thermoelectric figure of merit (ZT) and compression strength of the geopolymer. This suggests that metakaolin-based geopolymer with optimum content of 0.01 wt.% of carbon fibre has great potential in generating more energy, and a better energy harvesting material to be used.